Reflections on Language Documentation in the Chaco - Golluscio, Lucia Angela (2018)
This chapter focuses on field research aimed at documenting Chaco languages with varying degrees of vitality, specifically those spoken in Argentina and in the vicinity of the Argentinian/Paraguayan, Argentinian/Bolivian, and Paraguayan/Bolivian borders. The case studies here selected provide an overview of recent experiences conducted in Chaco within the framework of Himmelmann 1998’s foundational program on documentary linguistics and subsequent publications along these lines. We emphasize the results of collaborative research on equal grounds and a discourse-oriented approach to language documentation. Our reflections also highlight the current threatening situation of indigenous peoples and their languages and discuss the function of language documentation, preservation, and archiving in this fragile scenario, with a view to supporting community language use and transmission as well as ongoing and future research in South America.